Preliminary investigation into the biomechanics and EMG analysis of a setup in wrestling - Sho, I.; Yuta, G.; Ryo, I. (International Journal of Wrestling Science, 2025)
This preliminary study explored methods for evaluating the setup techniques for wrestling, which are critical for successful leg attacks. Two male collegiate wrestlers, who had placed in the top ranks at national-level student competitions, participated in simulated trials in which setup motions were executed and evaluated using both biomechanical and subjective measures. Three-dimensional motion capture and surface electromyography (EMG) were employed to assess the kinematic and muscular responses, while the visual analog scale (VAS) was used by three assessors—the attacker, defender, and a coach with competitive and coaching experience (the first author of this study)—to rate the quality of each setup. Moderate inter-rater agreement was observed in one the trials of one participant (Kendall`s W = 0.411, p = 0.016), whereas the other trial showed low agreement. Correlation analysis revealed that the kinematic features most strongly associated with the VAS scores varied among the assessors, suggesting differing evaluation criteria. EMG data showed consistent activation patterns, although quantitative comparisons were limited by the absence of a standardized reference point. These findings highlight the challenges of using subjective assessments alone to evaluate setup quality and suggest the need for objective kinematic indicators, such as vertical head acceleration, to standardize feedback and improve training. This study represents an early step toward developing reliable tools for analyzing and teaching setup movements during wrestling.